The effects of eccentric phase tempo in squats on hypertrophy, strength, and contractile properties of the quadriceps femoris muscle - Kojic, F.; Mandic, D.; Duric, S. (Frontiers in Physiology, 2025)
Introduction: The aim of the present study was to investigate the effects of eccentric phase tempo in squats on hypertrophy, strength, and contractile properties of the quadriceps femoris (QF) muscle.